Action Research and Project Approach: Journey of an Early Childhood Pre-service Teacher and a Teacher Educator - Ellie Wastin; H. Sophia Han (Networks: An Online Journal for Teacher Research, 2014)
The purpose of this article is to share an action research study conducted by an early childhood pre-service teacher in a Kindergarten classroom. There were dual goals for this action research: (a) to enhance preservice teacher’s questioning and classroom management strategies, and (b) to enhance Kindergarten children’s scientific inquiry and knowledge. A teacher guided mini-project approach was adopted as a main instructional methodology for a ‘Rain and Water Cycle’ project. Using video, we documented self-reflection and feedback. Through this experience, the pre-service teacher gained both knowledge and confidence. At the same time, the Kindergarten children took an active role in investigating the ‘Rain and Water Cycle’ through a variety of hands-on learning experiences. Based upon children’s work samples and other documentation, it was evident that their cognitive growth and learning, especially who were typically performing at the below grade level, was extensive. Challenges and possibilities related to pre-service teacher action research within the early childhood teacher preparation programs are shared. Ideas for adopting action research frameworks to reconceptualize early field internships are also discussed.